Aplikasi Inventarisasi Laboratorium Berbasis Web Menggunakan QR Code dan RFID di Laboratorium/Bengkel Teknik Telekomunikasi - Rabiah, Nur Nabila; Lindawati, Lindawati; Sarjana, Sarjana (Politeknik Ganesha Medan, 2022)
State Polytechnic of Sriwijaya is one of the universities that organize vocational education in Indonesia, by having a variety of laboratories to support its education. One of them is the Laboratory of Telecommunication Engineering Study Program, which has assets in the form of equipment/instruments used by its students to carry out practical activities based on predetermined courses. However, the current borrowing equipment system in the laboratory still uses a manual system, where students are required to fill out a loan form provided by the laboratory technician. In this case, the use of website-based applications as a medium for stock information and lending activities is expected to be an alternative in the inventory process. The prototype method is used in application development. Web-based applications are designed using the Laravel framework. After testing using a black box, it shows that all the functionality of the application system that has been designed runs properly and well. From the test results, the QR Code and RFID can display the scan results in the application quickly. A web-based inventory application with QR Code and RFID technology can assist in monitoring inventory and the process of borrowing equipment in the Telecommunication Engineering Study Program laboratory.